Sugar-Recognizing Ubiquitin Ligases: Action Mechanisms and Physiology - Yoshida, Yukiko; Mizushima, Tsunehiro; Tanaka, Keiji (Frontiers in Physiology, 2019)
F-box proteins, the substrate-recognition subunits of SKP1–CUL1–F-box protein (SCF) E3 ubiquitin ligase complexes, play crucial roles in various cellular events mediated by ubiquitination. Several sugar-recognizing F-box proteins exist in both mammalian and plant cells. Although glycoproteins generally reside outside of cells, or in organelles of the secretory pathway, these lectin-type F-box proteins reside in the nucleocytoplasmic compartment. Mammalian sugar-recognizing F-box proteins commonly bind to the innermost position of N-glycans through a unique small hydrophobic pocket in their loops. Two cytosolic F-box proteins, Fbs1 and Fbs2, recognize high-mannose glycans synthesized in the ER, and SCFFbs1 and SCFFbs2 ubiquitinate excess unassembled or misfolded glycoproteins in the ERAD pathway by recognizing the innermost glycans, which serve as signals for aberrant proteins. On the other hand, endomembrane-bound Fbs3 recognizes complex glycans as well as high-mannose glycans, and SCFFbs3 ubiquitinates exposed glycoproteins in damaged lysosomes fated for elimination by selective autophagy. Plants express stress-inducible lectin-type F-box proteins recognizing a wider range of N- and O-glycans, suggesting that the roles of mammalian and plant lectin-type F-box proteins have diverged over the course of evolution to recognize species-specific targets with distinct functions. These sugar-recognizing F-box proteins interpret glycans in the cytosol as markers of unwanted proteins and organelles, and degrade them via the proteasome or autophagy.